Diplomacy Blue Economy: Pengaruh Indian Ocean Rim Association (IORA) terhadap Keberlanjutan Kelestarian Laut Indonesia - Yolanda Yolanda; Atika Puspita Marzaman (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Indonesia as an archipelago country must pay attention to its policies and their impact on marine sustainability. This also includes its membership in various regional organizations, including the Indian Ocean Rim Association (IORA). Therefore, this article discusses the implementation of Indonesian policies with the blue economy concept which is studied through membership in IORA. This article aims to examine the influence of the implementation of the blue economy on the sustainability of Indonesia's seas. The method used is a literature study carried out with a qualitative-descriptive approach using maritime diplomacy and blue economy theories. The data used in this paper is secondary data which includes sources from books, journals, trusted and relevant websites as well as official and trusted news. There are challenges in implementing the blue economy in Indonesia, such as robbery, piracy and illegal fishing which can have a negative impact on marine sustainability, as well as marine pollution and unsustainable marine exploitation. So through maritime safety & security which includes piracy, armed robbery at sea, terrorism, decreasing marine sustainability, and exploitation of marine resources which are IORA's priority areas. The results of this research show that there are positive implications of Indonesia's blue economy concept with other IORA member countries for the sustainability of Indonesia's seas.